Your conflict matters to me! Behavioral and neural manifestations of control adjustment after self-experienced and observed decision-conflict - Winkel, Jasper; Wijnen, Jasper G.; Ridderinkhof, K. Richard; Groen, Iris I.; Derrfuss, Jan; Danielmeier, Claudia; Forstmann, Birte U. (Frontiers in Human Neuroscience, 2009)
In everyday life we tune our behavior to a rapidly changing environment as well as to the behavior of others. The behavioral and neural underpinnings of such adaptive mechanisms are the focus of the present study. In a social version of a prototypical interference task we investigated whether trial-to-trial adjustments are comparable when experiencing conflicting action tendencies ourselves, or simulate such conflicts when observing another player performing the task. Using behavioral and neural measures by means of event-related brain potentials we showed that both own as well as observed conflict result in comparable trial-to-trial adjustments. These adjustments are found in the efficiency of behavioral adjustments, and in the amplitude of an event-related potential in the N2 time window. In sum, in both behavioral and neural terms, we adapt to conflicts happening to others just as if they happened to ourselves.